Colombian centenarians: A Geohealth approach to longevity study - Clímaco de Jesús Pérez-Molina; Flor Elena Chavarro-Bermeo; Luis-Fernando Gutiérrez-Fernández; Santiago Galvis-Villamizar; Wanderley Augusto Arias Ortiz; Laura Cabezas-Pinzón; Carlos-Felipe Escobar-Roa (PLoS ONE, 2025)
Introduction Population longevity is a global phenomenon influenced by various factors including social, economic transitions, and medical advancements. The study focused on the population over 95 years old, adopting an approach that integrates data from the 2018 Census and geospatial analysis techniques. Methods An ecological study was conducted using anonymized microdata from the 2018 National Population and Housing Census (CNPV). Geographic analysis, choropleth maps, and Kernel density estimation were employed to identify clusters of individuals aged over 95 years. Results The study identified 43,427 individuals aged 95 years or older in Colombia, with concentrations observed in departments such as Antioquia and Bogotá. Analysis by department and municipality revealed variations in rates and sex distribution. Kernel density analysis highlighted clusters in the Valle de Tenza area and other regions. Conclusion This study sheds light on the geographical distribution of centenarians in Colombia, emphasizing clusters in certain regions. More research is needed to understand the individual and contextual factors underlying successful aging in Colombia and to inform policies to improve the quality of life of older populations.